Religious guidance for female migrant workers in Hong Kong through the Arisan Congregation Model and Regular Religious Lectures to strengthen religious spirituality - Dwi Widiastuti (Institut Studi Islam Muhammadiyah Pacitan, 2025)
Indonesian female migrant workers working abroad, particularly in Hong Kong, face various psychological, moral, and social challenges due to separation from their families and pressure from their work environment. Religious study groups and social gatherings are designed as spiritual and social development programs to help TKW overcome these pressures, increase their resilience, and strengthen their moral values. This program is held regularly every Saturday afternoon, with applicable religious study materials covering consistency in worship, strengthening of character, emotion management, maintaining self-respect, the role of family from a distance, and interpreting work as worship. The study circle method emphasizes active participant involvement through discussion, experience sharing, and personal guidance from facilitators. The social gathering, as a socio-economic activity, further strengthens solidarity and support networks among members. Evaluation is conducted informally through participant feedback, behavioral changes, and active involvement in activities, while program sustainability is maintained through a simple management structure and facilitator regeneration. The results of the activities show that religious recitation and social gatherings have a multidimensional positive impact, including increased inner peace, self-control, self-confidence, social solidarity, and the ability of participants to adaptively cope with life's pressures.